Ecomorphological study of Caribou (Rangifer tarandus caribou) distal phalanx: Insights from 3D geometric morphometrics for paleoenvironmental reconstructions - Ana Belén Galán López; Nicole Torres-Tamayo; María Fernanda Martínez-Polanco (Quaternary Environments and Humans)
Reindeer mobility patterns exhibit significant variability in modern ecosystems, especially between open and wooded environments. This variability makes it difficult to reconstruct past reindeer migration patterns, which is key to understand the role of reindeer herds in the sustenance and territorial organization of Prehistoric hunter-gatherer societies. By examining morphology associated with different habitats and movement patterns, insights into prehistoric reindeer behavior can be obtained. Investigating the relationship between locomotor anatomy and substrate type in present-day animals allows for paleoecological inferences, as previous research indicates that an animal's environment affects bone morphology. In the present study, 3D geometric morphometrics is employed to examine the influence of habitat type and mobility patterns on distal phalanx morphology from extant caribou (Rangifer tarandus caribou). Our analysis reveals significant morphological adaptations linked to different habitats (boreal forest, mountain, and tundra) and mobility types (sedentary, migratory, and altitudinal). However, the potential impact of sex remains uncertain due to incomplete data. The significant variations in shape and size of caribou distal phalanges across different habitats and mobility types underscore the complex interactions between morphology, ecology, and evolutionary pressures.